The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2486/indhealth.ms1150
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to Metal Fume, NO2, and O3 among Production Welders and Non-welders

Abstract: The objective of this study was to characterize personal exposures to welding-related metals and gases for production welders and non-welders in a large manufacturing facility. Welding fume metals and irritant gases nitrogen dioxide (NO 2 ) and ozone (O 3 ) were sampled for thirty-eight workers. Personal exposure air samples for welding fume metals were collected on 37 mm open face cassettes and nitrogen dioxide and ozone exposure samples were collected with diffusive passive samplers. Samples were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
4
6
1
1
Order By: Relevance
“…Only a few samples showed ozone levels higher than the background (Hedmer et al 2014). Low exposure levels to ozone and nitrogen oxide in welders’ environment have also been shown by Schoonover et al (2011). Ozone exposure is probably intermittent, and a few very short peaks would then not have been detected.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Only a few samples showed ozone levels higher than the background (Hedmer et al 2014). Low exposure levels to ozone and nitrogen oxide in welders’ environment have also been shown by Schoonover et al (2011). Ozone exposure is probably intermittent, and a few very short peaks would then not have been detected.…”
Section: Discussionsupporting
confidence: 52%
“…Adverse effects in the airways may be caused by gases as well as particles in the welding fumes (Antonini 2003), although particles may be the more prominent exposure (Schoonover et al 2011; Hedmer et al 2014). The size of the particles influences the deposition in the airways and the health effects (Oberdörster et al 2005; Sturm 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, not using a consumable electrode during TIG welding results in lower exposures. The highest average exposures occur in SMAW, followed by GMAW, and GTAW [21]. K. Fuglsang et al investigated the Fume Generation Rates (FGR).…”
Section: • -Materialsmentioning
confidence: 99%
“…These gases were collected on pre-treated filters with proper solutions. Then, NO 2 and O 3 were analyzed by spectrophotometry and ion chromatography (IC), respectively [21]. Azari et al conducted a study to evaluate exposure of mild steel welders to ozone and nitrogen oxides during TIG and MIG welding.…”
Section: Monitoring Of Welding Emissionsmentioning
confidence: 99%
“…Brand et al reported that the cellular effect parameters and macrophage concentration in induced sputum decreased with increasing NO 2 concentration with 4 consecutive weeks of exposure at 0.5 ppm (21). Schoonover et al, in a study on production welders and nonwelders, reported that welders were exposed to higher concentrations of NO 2 and O 3 , but this difference was not statistically significant (22). The results of risk assessment showed, risk managment to help identify and evaluate risks originated from chemicals usages.also risk managment to prevent, reduce, or minimize potential harm to the workplace.…”
Section: Discussionmentioning
confidence: 99%